2017
DOI: 10.1177/0040517517698985
|View full text |Cite
|
Sign up to set email alerts
|

Rotor spinning transfer channel design optimization via computational fluid dynamics

Abstract: The conventional rotor spinning unit generates flow vortices in the transfer channel upstream region which affect the fiber configuration and consequently yarn properties. Geometry and spinning parameters such as transfer channel length, inlet width, rotor outlet pressure, opening roller speed and diameter were found to be key parameters influencing airflow characteristics. To reduce the flow vortices in the upper stream region, modifications of the transfer channel were proposed, and their airflow fields were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…One comes from the bypass channel and the other is from the trash box. In reality, due to the new mass flow coming from the bypass channel, the mass flow from the trash box is smaller than the one existing in conventional units, in any case the overall mass flow is higher in the new developed unit, as proved in (Lin et al, (2018)). This allows higher average air velocity in the fiber transfer channel and decreases air velocity in the trash box.…”
Section: Rotor Spinning Unit and 3-d Cfd Modellingmentioning
confidence: 90%
See 4 more Smart Citations
“…One comes from the bypass channel and the other is from the trash box. In reality, due to the new mass flow coming from the bypass channel, the mass flow from the trash box is smaller than the one existing in conventional units, in any case the overall mass flow is higher in the new developed unit, as proved in (Lin et al, (2018)). This allows higher average air velocity in the fiber transfer channel and decreases air velocity in the trash box.…”
Section: Rotor Spinning Unit and 3-d Cfd Modellingmentioning
confidence: 90%
“…The occurrence of high recirculation in the transfer channel inlet area would degrade fiber straightness and consequently decrease yarn properties. (Lin et al, (2018)) further developed a three-dimensional CFD model of the rotor spinning unit to study the vortex inside the transfer channel. They reported that the vortices were decreased either increasing the transfer channel length or the rotor outlet relative pressure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations